Kinetic and temporospatial gait parameters in a heterogeneous group of dogs - Kano, Washington T. [UNESP]; Rahal, Sheila C. [UNESP]; Agostinho, Felipe S. [UNESP]; Mesquita, Luciane R. [UNESP]; Santos, Rogerio R. [UNESP]; Monteiro, Frederico O.B.; Castilho, Maira S. [UNESP]; Melchert, Alessandra [UNESP] (Springer Nature, 2016)
Background: A prime concern of the gait analysis in a heterogeneous group of dogs is the potential influence of factors such as individual body size, body mass, type of gait, and velocity. Thus, this study aimed to evaluate in a heterogeneous group of dogs a possible correlation of the stride frequency with kinetic and temporospatial variables, as well as the percentage of body weight distribution (%BWD), and compare symmetry index (SI) between trotting and walking dogs. Twenty-nine clinically healthy dogs moving in a controlled velocity were used. The dogs were organized into two groups based on duty factor. Group 1 comprised 15 walking dogs, aged from 9 months to 8 years and weighing about 22.3 kg. Group 2 had 14 trotting dogs, aged from 1 to 6 years and weighing about 6.5 kg. The kinetic data and temporospatial parameters were obtained using a pressure-sensing walkway. The velocity was 0.9-1.1 m/s. The peak vertical force (PVF), vertical impulse (VI), gait cycle time, stance time, swing time, stride length, and percentages of body weight distribution among the four limbs were determined. For each variable, the SIs were calculated. Pearson's coefficient was used to evaluate correlation between stride frequency and other variables, initially in each group and after including all animals. Results: Except for the %BWD (approximately 60 % for the forelimbs and 40 % for the hind limbs), all other parameters differed between groups. Considering each Group individually a strong correlation was observed for most of the temporospatial parameters, but no significant correlation occurred between stride frequency and PVF, and stride frequency and %BWD. However, including all dogs a strong correlation was observed in all temporospatial parameters, and moderate correlation between stride frequency and VI, and weak correlation between stride frequency and PVF. There was no correlation between stride frequency and %BWD. Groups 1 and 2 did not differ statistically in SIs. Conclusions: In a heterogeneous group of dogs conducted at a controlled velocity, the %BWD and most of SIs presented low variability. However, %BWD seems to be the most accurate, since factors such as the magnitude of the variables may influence the SIs inducing wrong interpretation. Based on results obtained from correlations, the standardization of stride frequency could be an alternative to minimize the variability of temporospatial parameters.
Keywords: Canine; Locomotion; Objective measurement; Velocity